1999
DOI: 10.1161/01.atv.19.12.2966
|View full text |Cite
|
Sign up to set email alerts
|

Human Apolipoprotein (Apo) B-48 and ApoB-100 Kinetics With Stable Isotopes

Abstract: Abstract-The kinetics of apolipoprotein (apo) B-100 and apoB-48 within triglyceride-rich lipoproteins (TRLs) and of apoB-100 within IDL and LDL were examined with a primed-constant infusion of (5,5,5-2 H 3 ) leucine in the fed state (hourly feeding) in 19 subjects after consumption of an average American diet (36% fat). Lipoproteins were isolated by ultracentrifugation and apolipoproteins by SDS gels, and isotope enrichment was assessed by gas chromatography/mass spectrometry. Kinetic parameters were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
95
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 42 publications
16
95
1
2
Order By: Relevance
“…From blood, plasma or lipoprotein samples, fatty acids (Bickerton et al, 2007), cholesterol (Beaumier-Gallon et al, 2001) or fat-soluble vitamins (Sauvant et al, 2003) or alternatively apoB-100 or apoB-48 (Welty et al, 1999) can be extracted and specific analyses made using various methods involving mass spectroscopy (GC-MS, GC-C-MS, LC-MS/MS-MS, etc). Determination of isotopic ratio in expired air (breath test) can also be done.…”
Section: Tracers With Stable Isotopesmentioning
confidence: 99%
“…From blood, plasma or lipoprotein samples, fatty acids (Bickerton et al, 2007), cholesterol (Beaumier-Gallon et al, 2001) or fat-soluble vitamins (Sauvant et al, 2003) or alternatively apoB-100 or apoB-48 (Welty et al, 1999) can be extracted and specific analyses made using various methods involving mass spectroscopy (GC-MS, GC-C-MS, LC-MS/MS-MS, etc). Determination of isotopic ratio in expired air (breath test) can also be done.…”
Section: Tracers With Stable Isotopesmentioning
confidence: 99%
“…The baseline kinetics for these subjects were reported previously. 18 The experimental protocol for in vivo stable-isotope kinetics, plasma lipid and lipoprotein characterization, quantification and isolation of the apolipoproteins, isotopic enrichment determinations, kinetic analysis, and statistical analysis were performed as previously described. 18 ApoE genotypes were determined by polymerase chain reaction amplification as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…The steady state enrichment of the plasma amino acid during the infusion may also be used; however, since its enrichment is usually greater than intracellular enrichment, a correction factor based on the apoB-100 plateau must be used. Welty et al (1999) have shown that the enrichment of VLDL apoB-100 at plateau is approximately 75% of that of plasma. Of note, VLDL apoB-100 does not reach a plateau in subjects with high VLDL (triglyceride) levels; therefore, one may assume that the relationship between the VLDL apoB-100 plateau and plasma amino acid enrichment is the same as in normal subjects assuming no abnormalities of amino acid metabolism.…”
Section: Stable Isotope Infusions: Primed Constant Infusion Versus Bolusmentioning
confidence: 99%
“…For further discussion of apoB-100 models, see the articles by Foster et al (1993) and Cobelli et al (1987). Welty et al (1999) present models for apoB-100 and apoB-48. apoA-I, A-II, and apoE models are currently under development by Welty and will be similar to the apoB-48 model (Welty et al, 1999).…”
Section: Stable Isotope Infusion Data Analysis and Modelingmentioning
confidence: 99%
See 1 more Smart Citation